(3GdLGeY aj eYQaI GdCOhjI hGdCZPjI GdeaQOIs - (3YHO Gddg Hf GdHOQ GdHjWGQ GdeUQj, GHf GdefPQ, CHh HcQ , J (B741 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CbGe HdWja MceJg HfjI GdEfSGf hHYO aEfg deG QSe HGdChGeQ GdeWGYI GdYGdjI HhVY cJGH ai GdCOhjI GdeaQOI s
(3BNQgG (B:s
(3jfeg CHh GdYHGS GdfHGJi Gdjfeg eYQhaI HGdbjQhGf hgj YfOge eNJHQI ai GdLQGMGJ hgj HfJg HjVGA hQbgG CRZH hGddg CYde s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B534s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs